Evaluation of the Promotional Activity of Cebuana Lhuillier Pawnshop in PH1 Bagong Silang Caloocan Caloocan City: Basis for Program Enhancement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A non-banking financial organization called Cebuana Lhuillier provides services like e-loading,pawnbroking, insurance, money remittance, and bill payment. Cebuana Lhuillier hassuccessfully positioned itself as the Philippines' top one-stop financial shop, driven by itsmission to give more Filipinos access to financial solutions and its vision to become the bestand most preferred micro-financial and business-to-business. Cebuana Lhuillier, the largestmicrofinance institution in the Philippines, has significantly encouraged innovation andentrepreneurship among its staff members by utilizing digital technologies.The evaluation of the promotional activity was "often" in terms of personal selling, advertising,Sales Promotion, public relations, and direct marketing. The biggest challenge encounteredby the consumer is the slowness of the process when there are a lot of people in CebuanaLhuillier. Cebuana Lhuillier needs to enhance the promotions that it offers to its customers.The recommendation that the researcher will make in Cebuana Lhuillier Ph1 is first to increasethe space of Cebuana Ph1 so that there are more customers who can transact and not crowdinside. Second, increase the number of employees within a Cebuana branch to speed upevery transaction; and last, have good communication or relationship with a customer so thatthere is no misunderstanding between the customer and the employee.
Keywords: Business